Musculoskeletal Education in Medical Schools: A Survey of Allopathic and Osteopathic Medical Students. (June 2018) - Sabesan, Vani J.; Schrotenboer, Andrew; Habeck, Jason; Lombardo, Daniel; Stine, Sasha; Jildeh, Toufic R.; Meiyappan, Arjun
Abstract : Background: Musculoskeletal (MSK) disorders are one of the most common causes of disability and emergency department and physician visits in the United States. However, there is very little consistency in how physicians in training are prepared to treat MSK disorders. On the basis of published reports, medical school graduates have a relative lack of cognitive mastery in MSK medicine, even with the recent increase in instruction. This study sought to compare MSK education at an allopathic medical school with that at an osteopathic medical school. Methods: An anonymous survey of students in medical school graduate years 2, 3, and 4 at Michigan State University College of Human Medicine (allopathic) and College of Osteopathic Medicine (osteopathic) was conducted. Questions were structured into three main categories: demographic information, content of the current MSK curriculum, and opinions regarding importance, instruction, and assessment of MSK education. Results: As of 2010, 83% of medical schools require MSK courses because of the United States Bone and Joint Initiative to incorporate such coursework into core curriculum. Yet only 54% of surveyed students thought that their MSK education was adequate. A greater portion of osteopathic students (57.1%) compared with allopathic students (26.8%) thought that their MSK curriculum is adequate, and as a consequence, 36.6% of allopathic students thought that they were inadequately prepared for the MSK content of US medical licensing examinations compared with 8.1% of osteopathic students. Further curriculum development and improvement is needed to advance physicians' abilities to address and treat MSK disorders. Medical students surveyed feel that this goal can be accomplished by emphasizing MSK education in third and fourth years of medical school. Conclusion: These findings highlight differences in MSK education between an allopathic and osteopathic medical school. Further standardization of the curriculum in medical schools may help improve the quality of teaching student comfort levels of new physicians. Level of Evidence: Level III